DAMPAK NARSISME PEMIMPIN TERHTERDAPATP KINERJA ORGANISASI: TINJAUAN LITERATUR MULTILEVEL PADA TINGKAT INDIVIDU, TIM, DAN ORGANISASI - Yuanus, Franki; Choirunnisa, Zuyyinna; Putra, Yudistira Ardi Nugraha Setyawan (Jurnal Governansi, 2025)
Leader narcissism is a multifaceted personality construct characterized by grandiosity and a need for admiration, which may interact with other traits within the "Dark Triad." In the context of leadership, narcissism exhibits paradoxical characteristics: on one hand, it can foster charisma and ambitious vision, even promoting positive ESG (Environmental, Social, and Governance) behaviors; on the other hand, excessive need for validation can lead to exploitative actions and significant negative outcomes. This literature review examines the multilevel impact of leader narcissism at the individual, team, and organizational levels—drawing upon Trait Activation Theory and Socioanalytic Theory. The findings indicate that leader narcissism can trigger counterproductive subordinate behaviors, increase team turnover, and affect organizational quality. However, political skill may serve as a moderating factor that enhances the functional expression of narcissism. This review identifies conceptual, methodological, and empirical gaps, and proposes future research directions to further elucidate the complexity of this phenomenon.